The effects of biofeedback training on athletes’ mental health and performance: a systematic review and Bayesian meta-analysis - Zhang, Xuda; Chang, Zhizhao; Zhao, Shiao; Ning, Ziheng (Frontiers in Psychology, 2025)
BackgroundBiofeedback and neurofeedback are increasingly used in sports psychology, yet their overall effectiveness for athletes’ mental health, athletic performance, and cognitive performance remains unclear.MethodsWe conducted a systematic review of randomized controlled trials across eight databases and performed Bayesian random-effects meta-analyses. Study selection used ASReview with the SAFE rule; full-text screening was done in Covidence; risk of bias followed Cochrane guidance; certainty of evidence was appraised with GRADE.ResultsForty-one studies met inclusion. Pooled effects were statistically significant across domains: mental health µ(SMD)=0.76 (95% CrI 0.44–1.09), athletic performance µ(SMD)=0.88 (0.69–1.05), and cognitive performance µ(SMD)=0.81 (0.48–1.14).ConclusionBiofeedback and neurofeedback benefit athletes across mental, athletic, and cognitive outcomes. Given heterogeneity and sample sizes, further rigorous trials are warranted to refine the estimates.Systematic review registrationPROSPERO registration CRD420251015094.